PENGARUH MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALTY TERHADAP MINAT BELAJAR SISWA PADA MATERI SISTEM TATA SURYA DI SEKOLAH DASAR - Jeliya dwita; Faizal Chan; Issaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to analyze the effect of using Augmented Reality (AR)-based learning media on students’ learning interest in the solar system topic at the elementary school level. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects were 40 sixth-grade students of SDN 14/I Sungai Baung, consisting of an experimental class and a control class. Data were collected using a learning interest questionnaire administered before and after the treatment. The data were analyzed using paired sample t-tests and independent sample t-tests. The results indicated a significant difference in learning interest between students who participated in learning using AR-based media and those who received conventional instruction. The significance value of the independent sample t-test was 0.001 (< 0.05), indicating that AR-based learning media had a significant effect on students’ learning interest. Therefore, Augmented Reality-based learning media can be used as an innovative alternative to enhance elementary school students’ learning interest in IPAS instruction.